EFFECTIVENESS OF EDUCATIONAL MEDIA INSTAGRAM REELS AND TIKTOK ON KNOWLEDGE TO PREVENT IRON DEFICIENCY ANEMIA - Pibriyanti, Kartika; Sukowati, Dewi; Rooiqoh, Qothrunnadaa Fajr; Pinasti, Ladyamayu; Luthfiya, Lulu’; Mufidah, Indahtul; Fathimah; Fadholah, Amal (Universitas Airlangga, 2025)
The lack of knowledge about iron deficiency anemia is caused by a lack of media that can open up public knowledge about the importance of this. As the industrial era 4.0 progresses, many digital media have emerged as a means to educate the public about preventing iron deficiency anemia, one of which is health promotion media in the form of video media Instagram Reels and TikTok. This study aims to determine the effectiveness of Instagram Reels and TikTok educational media on knowledge about preventing iron deficiency anemia in adolescent girls. The research used quasi experiment method with a pre-posttest group design. The sample amounted to 105 respondents (Instagram Reels n:35, TikTok n:35, and leaflet n:35. Knowledge data were obtained by filling out pre and posttest questionnaires, processed using the Wilcoxon test. The mean difference between the three groups used Kruskal-Wallis and Post Hoc Mann Whitney tests. The effectiveness of the three media was tested using the N-Gain Score. The results of the pre and post-test research on the three media had p-value 0.000 which shows an increase in knowledge. The frequency distribution of knowledge in the TikTok group was 100%, Instagram Reels 94.3% and leaflets 51.4%. The effectiveness test of the N-Gain score of TikTok media is 81% including it in the effective category, Instagram Reels is 60% including in the moderately effective category and leaflets are 28% including in the ineffective category. The conclusion is that TikTok media is most effective compared to Instagram Reels media and leaflets.